The Impact of Personality on Job Satisfaction: A Study of Executive Employees in Selected Private Hospitals in Colombo East, Sri Lanka - *, Balasuriya; G.D.N, Perera, (IJRDO - Journal of Business Management, 2016)
This study intends to investigate the impact of personality on job satisfaction among executives in the selected private hospitals in Colombo East, Sri Lanka .The independent variable is the types of personality with five major personality factors; extraversion, agreeableness, openness to experience, neuroticism and conscientiousness. The dependent variable is the job satisfaction. Data were collected from 175 executives in the selected private hospitals in Colombo East, Sri Lanka. For measuring study variables, the convenience sampling method is selected and the self-administered structured questionnaires are developed. Next data thus collected were analyzed under the statistical data analysis package of 16 using correlation and regression methods. The findings of the study suggested that the personality types of extraversion, agreeableness, openness to experience and conscientiousness of executive employees had significant positive impact and neuroticism type had significant negative impact on job satisfaction. Further, all hypotheses of the study are empirically accepted. Hence, 43.3% of the variation in job satisfaction can be explained by the big five personality factors.